2018
DOI: 10.3201/eid2401.161758
|View full text |Cite
|
Sign up to set email alerts
|

Nipah Virus Contamination of Hospital Surfaces during Outbreaks, Bangladesh, 2013–2014

Abstract: Nipah virus (NiV) has been transmitted from patient to caregivers in Bangladesh presumably through oral secretions. We aimed to detect whether NiV-infected patients contaminate hospital surfaces with the virus. During December 2013–April 2014, we collected 1 swab sample from 5 surfaces near NiV-infected patients and tested surface and oral swab samples by real-time reverse transcription PCR for NiV RNA. We identified 16 Nipah patients; 12 cases were laboratory-confirmed and 4 probable. Of the 12 laboratory-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…In humans, severe acute respiratory sickness and/ or encephalitis can be provoked by a bat-borne zoonotic, paramyxoviral pathogen NiV. 13,14 This negative-sense single-stranded RNA virus belongs to the family Paramyxoviridae, genus Henipavirus and is closely related to Hendra viruses. 13,15 Like Hendra virus, NiV may also cause fatal pneumonia or an acute respiratory-distress-like syndrome.…”
Section: Cellular and Molecular Changes In Niv Infectionmentioning
confidence: 99%
“…In humans, severe acute respiratory sickness and/ or encephalitis can be provoked by a bat-borne zoonotic, paramyxoviral pathogen NiV. 13,14 This negative-sense single-stranded RNA virus belongs to the family Paramyxoviridae, genus Henipavirus and is closely related to Hendra viruses. 13,15 Like Hendra virus, NiV may also cause fatal pneumonia or an acute respiratory-distress-like syndrome.…”
Section: Cellular and Molecular Changes In Niv Infectionmentioning
confidence: 99%
“…Evidence indicated that human-to-human transmission resulted from direct contact with respiratory secretions of severely ill patients 39–42. NiV can persist on surfaces, posing further risk for fomite-borne NiV transmission 43…”
Section: Introductionmentioning
confidence: 99%
“…Nipah virus was first discovered in a large encephalitis outbreak in Malaysia in 1998 [2][3][4]. Nipah virus outbreak has been recognized nearly every year in Bangladesh since 2001 and occasionally in neighboring India [5][6][7][8][9]. With the capacity of person-to-person transmission, high case fatality rate (>70%) and no availability of treatment or vaccine, the World Health Organization included the Nipah virus among the 7 Blueprint list of priority diseases and effort for Nipah vaccine development is underway [10-12].…”
Section: Introductionmentioning
confidence: 99%